The Return of the Pink Panther - Edwards, Blake, 1922-; Schell, Catherine; Christopher Plummer; Herbert Lom; Peter Sellers (UK Incorporated Television Company (ITC), 1975)
That famous jewel, The Pink Panther, has once again been stolen and Inspector Clouseau is called in to catch the thief. The Inspector is convinced that `The Phantom' has returned and utilises all of his resources - himself and his oriental manservant - to reveal the true identity of `The Phantom'.
Inspector Clouseau is put on the case when the Pink Panther diamond is stolen, with the Phantom's trademark glove the only clue.
Frank Waldman
Language(s): English Subtitle(s): English
Keywords: Comedy